Single low-dose ketamine infusion for women with prenatal depressive symptoms undergoing cesarean delivery: A pilot randomized trial - Wang, Shuo; Deng, Chun-Mei; Zeng, Yuan; Ma, Jia-Hui; Qu, Yuan; Wang, Dong-Xin (Frontiers in Surgery, 2022)
Background: Ketamine is approved for antidepressant therapy, but evidence regarding its use in women with perinatal depression is lacking. Herein, we investigated the effects of low-dose ketamine in women with prenatal depression and tested the feasibility of a future large randomized trial. Methods: This was a randomized, double-blind, placebo-controlled pilot trial. Sixty-six women with prenatal depression who were scheduled for elective cesarean delivery were randomized to receive either placebo (normal saline) or low-dose ketamine (0.5 mg/kg). The study drugs were infused over a 40-minute period after clamping the umbilical cord. The primary outcome was depression score assessed with the Edinburgh Postnatal Depression Scale at 48 h postpartum. Among other and safety outcomes, occurrence of nausea or vomiting was observed, pain intensity was assessed with the numeric rating scale. The feasibility of implementing the protocol was also evaluated. Results: A total of 64 parturients were included in the intention-to-treat analysis. The depression score at 48 h did not differ between groups: median 8 (interquartile range 6 to 10) with placebo versus 9 (6 to 13) with ketamine; median difference 1, 95% CI -1 to 3; P=0.608. The pain intensity at 4 h postpartum was less severe in the ketamine group (median difference -1, 95% CI -1 to 0, P=0.002). Among safety outcomes, intraoperative nausea or vomiting was less common in patients given ketamine (21.2% [7/33] with placebo versus 0.0% [0/33] with ketamine, P=0.011). Recruitment was satisfactory and the protocol was acceptable to participants and clinicians. Conclusions: A single low-dose ketamine infusion did not decrease the depression score at 2 days, but reduced intraoperative nausea and vomiting and lowered pain intensity at 4 h after cesarean delivery in women with prenatal depression. The study protocol is feasible for a large randomized trial.